THE LEVEL OF IMMUNOGLOBULINS IN THE ORAL FLUID OF PATIENTS WITH SECRETORY IMMUNOGLOBULIN A DEFICIENCY AND GENERALIZED PERIODONTITIS - H.M. Sylenko; P.M. Skrypnikov; Yu.I. Sylenko; O.V. Izmailova; B.Yu. Sylenko (Український стоматологічний альманах)
One of the major challenges in dentistry is generalized periodontitis (GP). Periodontitis is characterized by the destruction of connective tissue, loss of periodontal attachment, and resorption of alveolar bone. Tissue destruction in periodontal diseases occurs as a result of the action of pathogenic microflora and the interaction of the immune and inflammatory response. The immune system is activated to protect against local microbial attack and the products of their destruction as a result of the spread or penetration into the gingival tissues.